Factores familiares asociados al consumo de sustancias psicoactivas en adolescentes escolarizados del departamento de la guajira (2021)
The general objective of this project is to establish the relationship between family aspects and the consumption of psychoactive substances in school adolescents in the department of La Guajira with a quantitative approach and a non-experimental design, the APGAR Family questionnaire and CRAFFT Scale were applied to a total than 58 young people from the department of La Guajira, Colombia. A level of no risk (53%) was evidenced in the face of the risk of consumption, the family functionality is 78% in its majority and the parenting style by the parents varies from negligence to authoritarian. The foregoing concludes that there is a relationship between both variables, but under certain factors and conditions. Keywords: Family, Consumption, Psychoactive substances and Adolescents